A novel thermal hydrolysis process for extraction of keratin from hog hair for commercial applications. (1st March 2020) - Tasaki, Ken
Highlights: A two-step thermal hydrolysis process has been developed to extract keratin from hog hair. We have achieved it without the use of chemicals. The recovery yield was comparable to one of the best yields by chemical processes. Abstract: We have developed a novel thermal hydrolysis process (THP) to extract and hydrolyze keratin from keratinous animal body wastes without using any chemicals. Our process consists of two heating steps: one is to swell and denature the keratin protein network in the intermediate filaments, while the other is to cleavage the disulfide bonds that connect the tight keratinous fibrils together. Using hog hair as an example, the two-step process achieved a nearly 70% keratin recovery yield, with respect to the original keratin in the hog hair, which is comparable to one of the best recovery yields by conventional chemical processes. The extracted keratin hydrolysate by THP was filtered by the shear wave-induced membrane ultrafiltation for characterization. The molecular weight (MW) analysis using SDS-PAGE and MALDI-TOF mass spectroscopy has demonstrated that our keratin hydrolysis obtained by our two-step THP has a wide range of MW distribution, similar to those already in the hair-care product market. The amino acid composition analysis has shown that our keratin hydrolysate by THP had twice as much essential amino acids as soybean meals on a dry mattter basis. As to the cysteine residue content, we have shown that it can be controlled by adjusting the 2nd heating temperature.